Punitive Processes? Judging in Thai Lower Criminal Courts. Issue 2 (21st June 2021) - McCargo, Duncan
Abstract: This article examines how Thai courts of the first instance deal with run-of-the-mill criminal cases. How do judges deal with criminal trials of a rather routine nature, often involving defendants from ethnic minorities and reflecting the particular conditions in the provinces concerned? Drawing on participant observation and interview research conducted mainly in two provinces in different regions of the country, the article examines the challenges faced by judges and court officials in dealing with heavy caseloads in a highly bureaucratized system where acquittal rates are extremely low. How far do such cases shed light on how judging is carried out in the majority of Thai courts? What kind of challenges do Thai judges face in adjudicating minor but often messy cases in order to fulfil societal expectations in line with their own understandings of justice?